Developments in the CARICOM Common Market : report to the WTO Council on Trade in Goods and Committee on Regional Trading Agreements ([CCS] [Georgetown]GY, 1999)
Presents an overview of the CARICOM Common Market. Examines trade provisions, trade in services and bilateral and multilateral agreements with non-members viz. Venezuela, Colombia, Dominican Republic, and the Free Trade Area of the Americas.
DC